2014
DOI: 10.1155/2014/436242
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Hepatic Fibrosis

Abstract: Hepatic fibrosis is a leading cause of morbidity and mortality worldwide. Hepatic fibrosis is usually associated with chronic liver diseases caused by infection, drugs, metabolic disorders, or autoimmune imbalances. Effective clinical therapies are still lacking. Autophagy is a cellular process that degrades damaged organelles or protein aggregation, which participates in many pathological processes including liver diseases. Autophagy participates in hepatic fibrosis by activating hepatic stellate cells and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 104 publications
0
44
0
Order By: Relevance
“…Recent data indicate that autophagy is a regulatory pathway in liver fibrosis, with profibrogenic effects related to a direct contribution of HSCs activation . Autophagy may supply energy for the activation of HSCs by delivering triglyceride and other components in lipid droplets from autophagosomes to lysosomes for degradation . Increased autophagy is observed in mice with liver injury induced by CCl 4 or thioacetamide, and loss of autophagic function by attenuated expression of Atg7 results in a reduction of fibrogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Recent data indicate that autophagy is a regulatory pathway in liver fibrosis, with profibrogenic effects related to a direct contribution of HSCs activation . Autophagy may supply energy for the activation of HSCs by delivering triglyceride and other components in lipid droplets from autophagosomes to lysosomes for degradation . Increased autophagy is observed in mice with liver injury induced by CCl 4 or thioacetamide, and loss of autophagic function by attenuated expression of Atg7 results in a reduction of fibrogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that autophagy may play a role in the regenerative potential of stem cell therapy939. Jung et al reported that the mechanism by which human placenta-derived MSCs promote tissue regeneration may involve HIF-alpha and autophagy, with autophagy being induced in CCl 4 -damaged hepatic cells in a hypoxia-dependent manner9.…”
Section: Discussionmentioning
confidence: 99%
“…Along with HSCs activation, autophagy flux is up‐regulated. Autophagy may supply energy for activation of HSCs by delivering triglyceride and other components in lipid drops from autophagosomes to lysosomes for degradation 19, 20. Hernández‐Gea et al .…”
Section: Discussionmentioning
confidence: 99%